IGNEOUS ALBITITE DIKES IN OROGENIC LHERZOLITES, WESTERN PYRÉNÉES, FRANCE: A POSSIBLE SOURCE FOR CORUNDUM AND ALKALI FELDSPAR XENOCRYSTS IN BASALTIC TERRANES. 1. MINERALOGICAL ASSOCIATIONS - Monchoux P.; Fontan F.; De Parseval P.; Wang R.C.; Martin R.F. (My University, 2006)
Dikes of albitite cross-cut two massifs of serpentinized lherzolite in the Pyrénées, France. At Espéchèe (Hautes-Pyrénées), they are corundum-bearing, whereas at Urdach (Pyrénées-Atlantiques), some dikes contain corundum, others do not. The majority of the minerals described here occur in both types of albitite. Albite is predominant, associated with muscovite and biotite, and with chlorite, epidote, zircon, titanite, thorite, pyrochlore (s.l.), aeschynite-(Ce), ferrocolumbite, rutile, ilmenite and magnetite as accessory phases. The epidote shows very high Sr contents (3 to 6 wt%, and up to 8.8 wt% SrO). However, certain minerals seem more specific to one type of dike. In corundum-bearing albitite, ilmenorutile, samarskite (s.l.), manganocolumbite, fersmite and fergusonite-(Y) are found, whereas in corundum-free albitite, allanite-(Ce), chevkinite-(Ce), apatite and monazite-(Ce) are developed. There are also subtle differences between corundum-bearing albitites of Urdach and Espéchère: the composition of samarskite (s.l.) varies from samarskite-(Y) (Urdach) to ishikawaite (Espéchère), but the two may be altered to calciosamarskite. Likewise, the composition of pyrochlore (s.l.) shows a strong variation, from weakly light-REE-enriched betafite and pyrochlore (Urdach) to Pb-, U-rich pyrochlore (s.s.) (Espéchère). The textures, dominantly pegmatitic, reflect a rapid magmatic crystallization, large crystals of albite predating the fine-grained carriers of Ca, Sr, Fe, Mg, Zr, Ti, Y, REE, U and Th.
Keywords: ALBITITE; CORUNDUM; DIKES; ESPÉCHèRE; FRANCE; ISHIKAWAITE; LHERZOLITE; PYRÉNÉES; PYROCHLORE-GROUP MINERALS; SAMARSKITE; STRONTIAN EPIDOTE; THORITE; URDACH; ZIRCON